2022
DOI: 10.1029/2021jg006555
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Importance of Denitrification for N2O Production in Soils Using Natural Abundance and Isotopic Labeling Techniques

Abstract: Nitrous oxide (N2O), a potent greenhouse gas that contributes significantly to climate change, is emitted mostly from soils by a suite of microbial metabolic pathways that are nontrivial to identify, and subsequently, to manage. Using either natural abundance or enriched stable isotope methods has aided in identifying microbial sources of N2O, but each approach has limitations. Here, we conducted a novel pairing of natural abundance and enriched assays on two dissimilar soils, hypothesizing this pairing would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…48 ). At the end of the incubation period, we mixed each jar and gas bag's air by attaching a 60 ml syringe to the jar's gas sampling port and, by opening the stopcock valve connecting the jar headspace to the gas bag, then we pumped the syringe for ~ 60 seconds to homogenize the jar headspace and Tedlar gas bag(Stuchiner and von Fischer 2022b). At the time of sampling, we connected our in-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…48 ). At the end of the incubation period, we mixed each jar and gas bag's air by attaching a 60 ml syringe to the jar's gas sampling port and, by opening the stopcock valve connecting the jar headspace to the gas bag, then we pumped the syringe for ~ 60 seconds to homogenize the jar headspace and Tedlar gas bag(Stuchiner and von Fischer 2022b). At the time of sampling, we connected our in-…”
mentioning
confidence: 99%
“…Stuchiner and von Fischer (2022b) we provide a detailed description of our incubation apparatus, which includes a 1 L Tedlar gas bag attached to the jar headspace to allow for removal of a large quantity of air for subsequent [N 2 O] and isotopic analysis with our laser-based analyzer (see Section 2.4.3 for details). Prior to incubation, we flushed and filled tion (details in Section 2.4.4).…”
mentioning
confidence: 99%
“…Nevertheless, we lack information to be able to source partition the N 2 O generated in this study. Recent advances in N 2 O isotopomer measurements are shedding light on microbial source partitioning of N 2 O, for example, Stuchiner and von Fischer ( 2022b ) demonstrate denitrification was the predominant N 2 O production pathway in soils ranging from 50% to 95% WFPS and Harris et al ( 2021 ) found that he proportion of N 2 O from denitrification did not decrease under even very low WFPS.…”
Section: Discussionmentioning
confidence: 99%